Les installations portuaires romaines d’Irun/Oiasso (Pays basque, Espagne) : entre équipement fonctionnel et façade urbaine - Mertxe Urteaga (Gallia)
In the border town of Irun/Oiasso (Basque Country, Spain), located on the left bank and 6 km from the mouth of the Bidasoa River, evidence of the first Roman port on the Iberian Peninsula and in the Bay of Biscay were discovered in 1992. This discovery marked a turning point in the recognition of the Roman past within Basque territories of the Atlantic coast. Their presence had until then been denied or considered marginal. The breadth of archaeological evidence found in Irun has given significant visibility to the existence of different types of port facilities and this research has extended to other geographic areas. To date, information has been obtained on three harbor areas and a half a dozen other facilities, and allows for differentiation between dry docks, breakwater jetties, slipway jetties and small platforms. The archaeological context is also very rich, composed of thousands of ceramic fragments and other important collections, including wooden objects, seed and textile remains... Archaeological endeavors were not limited to the port area; indeed, they were undertaken across the entirety of the historic center of Irun according to the tenets and methods of rescue archeology. In this environment, significant remains of urban constructions were discovered, including, most importantly, the traces of a substantial urban remodeling that took place at the end of the 1st c. AD. It was a process of comprehensive transformation, that created a horizontal terrace 600 m long and 350 m wide: for which, the unequal terrain was levelled, surplus soil from hilly areas being used to raise depressed levels. On this flattened ground the settlement was built following an ordered layout and including characteristic elements of this kind of urban environment, such as public bathhouses. The port facilities are contemporary to one another and prior to these constructions, the shores of the estuary were previously lacking in such infrastructure. Micropaleontological studies on benthic foraminifera present in the sediments collected during the archaeological excavations, trace the evolution of sedimentation and shed light on the process of filling these harbor zones. Analysis of the tidal cycles allows us to understand that, in some cases such as the Tadeo Murgia multi-level dock, the facilities were built on the edge of the estuary, in an area accessible only at high tide. Its use was therefore limited to a relatively short period and varied depending on the lunar cycles. These observations have led to the suggestion that these installations may have been built as contributions toward the development of monumentality within the settlement.